2019
DOI: 10.1017/s2040174419000096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intrauterine growth restriction and postnatal nutrition on pediatric asthma in Bangladesh

Abstract: Numerous studies have investigated the risk of developing asthma due to early-life experiences and environmental exposures. However, the influence of intrauterine growth restriction and postnatal undernutrition on childhood wheezing/asthma remains unclear. Thus, we examined the effects of both small for gestational age (SGA) and postnatal stunted growth on ever asthma among children in the rural areas in Bangladesh.Multiple follow-up studies were conducted in a cohort of randomized clinical trial of nutrition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(45 reference statements)
1
1
0
Order By: Relevance
“…More recently asthma prevalence has been reported as high as 20.2% and 6.8% in 4.5 and 10 years old, respectively. 40 These are higher than the estimates reported here; however, an asthma prevalence of 8.7% in 5 years from the same surveillance site was also reported, similar to the prevalence we report here. 41 These differences in prevalence could be due to environmental variation between the research sites within the country.…”
Section: Discussionsupporting
confidence: 85%
“…More recently asthma prevalence has been reported as high as 20.2% and 6.8% in 4.5 and 10 years old, respectively. 40 These are higher than the estimates reported here; however, an asthma prevalence of 8.7% in 5 years from the same surveillance site was also reported, similar to the prevalence we report here. 41 These differences in prevalence could be due to environmental variation between the research sites within the country.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, secondhand smoke in childhood does not fully explain the association between low SES and the risk of lung disease and lung cancer. Second, the low SES of parents is associated with intrauterine growth restriction and delayed pulmonary development,42 which increase the risk of pulmonary diseases such as asthma and COPD or cause a decrease in lung function 42–44. Third, low SES is closely associated with an increased risk of respiratory infections in childhood and adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the low SES of parents is associated with intrauterine growth restriction and delayed pulmonary development, 42 which increase the risk of pulmonary diseases such as asthma and COPD or cause a decrease in lung function. [42][43][44] Third, low SES is closely associated with an increased risk of respiratory infections in childhood and adulthood. Recent studies have reported that respiratory tract infection in childhood may cause decreased pulmonary function and increase the risk of asthma and COPD.…”
Section: Open Accessmentioning
confidence: 99%